ANALISIS EFEKTIVITAS SISTEM PENGEMBALIAN REKAM MEDIS RAWAT INAP BERBASIS WEB PADA RUMAH SAKIT UMUM BALI ROYAL - Ni Putu Indah Pratiwi (Health Care Media, 2022)
The return of medical record inpatients is the early process of medical record file process. Standard operational procedure of return medical record at Public Hospital Bali Royal is 1x24 hours after the patients go home. The return of medical record files in a month at 659 documents consist of 492 files are not late (75)%) and 167 files are late (25%). The record of return is still conducted manually on expedition book without monitoring medical record return. The purpose of this study is to know the effectivity of medical record return system on inpatients web base to the number of medical record delay return at Public Hospital Bali Royal. This research is qualitative used Pre Experimental Design by using System Development Life Cycle (SDLC). The result implemented usability test show value percentage 80.37% that can be categorized ‘Good”. The result Wilcoxon signed rank test obtained significant value at 0.00 so the value 0.00 is smaller (<) 0.05. It can be concluded form this research that the system usage of medical record return inpatients wed base effective to delay rate of medical record return by giving return notification on inpatients medical record.